Analysis of Park-Integrated Sidewalk User Behavior Using the Person-Centered Mapping Method: The Case of : Sultan Hasanuddin Street, Makassar, Indonesia - End, The; Hasrydha; Opu, Andi Besse (Dewantara Journal of Technology, 2025)
Sidewalk is a space at the side of the road specifically designed for pedestrians, ensuring a sense of safety and comfort. In several locations in Makassar, Indonesia, many sidewalks are directly integrated with open spaces such as parks, creating a pattern of movement that differs from that of typical sidewalk users. Sidewalks are intended to facilitate pedestrian activities, but the reality on the ground doesn't always meet expectations. Pedestrians often encounter obstacles on the sidewalk, disrupting their walking activities. This research identifies the behaviors of pedestrians in a park-integrated sidewalk in Makasssar, Indonesia. Data was gathered through literature, interviews, questionnires, observations and documentations. It uses observations based on predetermined research indicators and analyze them using behavior-mapping theory. An evaluation was also carried out by the community respondents which was used as a measurement indicator using This study identifies pedestrian behavior on sidewalks integrated with parks in Makassar City, Indonesia. Data were collected through literature, interviews, questionnaires, observation, and documentation. This study employed observational techniques based on predetermined research indicators and analyzed using behavior mapping theory, specifically Person-Centered Mapping, which focuses on the movements or behaviors of specific individuals/groups over time. Findings were validated through triangulation of data sources involving observation, documentation, and interviews. The research findings indicate several types of behavior on sidewalks integrated with parks. These behaviors tend to vary and are influenced by the sidewalk's environmental conditions, particularly its use as a venue for sales activities and vehicle parking.